2018
DOI: 10.1016/j.biomaterials.2017.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy based on fucoidan-functionalized polymer nanoparticles targeting P-selectin

Abstract: Injection of recombinant tissue plasminogen activator (rt-PA) is the standard drug treatment for thrombolysis. However, rt-PA shows risk of hemorrhages and limited efficiency even at high doses. Polysaccharide-poly(isobutylcyanoacrylate) nanoparticles functionalized with fucoidan and loaded with rt-PA were designed to accumulate on the thrombus. Fucoidan has a nanomolar affinity for the P-selectin expressed by activated platelets in the thrombus. Solid spherical fluorescent nanoparticles with a hydrodynamic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 62 publications
2
92
0
Order By: Relevance
“…17 Recently, the group of Letourneur demonstrated that fucoidan-labeled polymeric nanoparticles exhibit a strong tropism for the clot fibrin network and facilitate vessel recanalization. 18 Non-organic nanoparticles have also been used for thrombolysis. Clusters of iron oxide nanocubes, coated and stabilized by a tPA multi-layer, were proposed by the authors for the combined chemical and thermal treatment of blood clots upon stimulation with exogenous alternating magnetic fields.…”
mentioning
confidence: 99%
“…17 Recently, the group of Letourneur demonstrated that fucoidan-labeled polymeric nanoparticles exhibit a strong tropism for the clot fibrin network and facilitate vessel recanalization. 18 Non-organic nanoparticles have also been used for thrombolysis. Clusters of iron oxide nanocubes, coated and stabilized by a tPA multi-layer, were proposed by the authors for the combined chemical and thermal treatment of blood clots upon stimulation with exogenous alternating magnetic fields.…”
mentioning
confidence: 99%
“…Aiming at reducing the side‐effects of tPA, polymeric nanoparticles (poly(isobutyl cyanoacrylate)) were used for its delivery to the thrombus. In this study it was shown that these nanoparticles after their functionalization with a P‐selectin molecule (fucoidan), enhanced thrombolysis. However, no data concerning ischemia were presented.…”
Section: Biomaterial‐based Approachesmentioning
confidence: 89%
“…CAMs are grouped into several families, namely, immunoglobulins, cadherins, integrins, selectins and ECM proteins (Table 1). 38,39,48,[40][41][42][43][44][45][46][47] These proteins can mediate cell adhesion by heterophilic (between cells of a different type) and homophilic (between cells of a single type) interactions. CAMs have specific affinities for cell surface glycoproteins, helping the specific location of cells within the tissues and transport of biochemical information to coordinate homeostasis including signal transduction, cellular communication, and recognition.…”
Section: Cellular Recognition and Adhesion Peptidesmentioning
confidence: 99%
“…84 Juenet et al produced polymer nanoparticles using the polysaccharide fucoidan (Fuco-NPs) to target P-selectin. 42 These nanostructures showed enhanced thrombolytic efficiency with overexpression of P-selectin.…”
Section: Cellular Recognition and Adhesion Peptidesmentioning
confidence: 99%